Analisis Strategi Pemasaran Islam Dalam Meningkatkan Penjualan: (Studi pada Toko Qolbi Muaro Jambi) - Nurvaizah Nurvaizah; Agustina Mutia; Solichah (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
Marketing strategy is something that is very important and has an influence on a business or enterprise. Competition in the business world is currently growing very rapidly, companies are required to take strategic steps to be able to compete under any conditions. Apart from the demands of competing, companies are also required to have advantages that can differentiate one company from another. According to sharia principles, marketing activities must be carried out or based on the spirit of worshiping Allah Swt, trying as much as possible for the common welfare, not for group interests, let alone personal interests. This research aims to describe the analysis of Islamic marketing strategies in increasing sales at the Qolbi Muaro Jambi Shop. Data collection techniques used interview and documentation methods from 25 respondents consisting of shop owners, employees and consumers of the Qolbi Shop. This research uses qualitative methods for primary and secondary data. The results of this research can be concluded that the analysis of Islamic marketing strategies to increase sales at the Qolbi Muaro Jambi Store has been carried out according to sharia. The marketing strategy carried out by Toko Qolbi Muaro Jambi uses sharia marketing strategy, namely segmentation, targeting and positioning.